Gold-catalyzed Hiyama coupling of (1-silyl)allylboronates with diazonium salts - Zhang, Shan; Wunsch, Jonas; Rominger, Frank; Rudolph, Matthias; Liu, Yaowen; Hashmi, A. Stephen K. (Organic chemistry frontiers, 2026)
The gold-catalyzed cross coupling of diazonium salts enables the selective coupling of silyl over boryl moieties. So far only aryl and vinyl B,Si-bifunctional building blocks have been coupled to obtain the silyl coupling product in an orthogonal manner to the boryl coupling product from palladium catalysis. To further broaden the synthetic utility of this concept, we herein extended this principle towards B,Si-bifunctional (1-silyl)allylboronates as reagents, which enable the conversion of aniline derivatives to synthetically valuable alkenyl boronates via their respective diazonium salt. The reaction, which shows a perfect preference for the silyl coupling precedes at room temperature and noteworthy without the typical assistance of light. Initial mechanistic investigations suggest that (1-silyl)allylboronate induces radical oxidative addition of diazonium salts to the gold catalyst.
Zuerst veröffentlicht: 15. November 2025
Gesehen am 26.01.2026